"lncidentaloma" of the adrenal gland - Santos, H. (1997)
Making greater use of Computerized Axial Tomography and Magnetic Resonance Imaging has increased the number of accidental discoveries of adrenal masses, which has become a serious problem in the approach and clinical behaviour towards patients. The authors report a clinicai case of a healthy 30 years old pregnant woman who was submit ted to a routine abdominal and pelvic ultrasound, which showed a solid mass in the right adrenal gland. After having made severa/ screening tests, a pheochromocytoma is diagnosed, which is surgically removed. The authors also discuss the strategy of clinical investigation, towards the incidental discovery of an adrenal mass.